Impact of flare on radiographic progression after etanercept continuation, tapering or withdrawal in patients with rheumatoid arthritis. (30th June 2019) - Smolen, Josef S; Pedersen, Ronald; Jones, Heather; Mahgoub, Ehab; Marshall, Lisa
Abstract: Objectives: The structural consequences of flare after dose reduction/discontinuation of biologic DMARDs in patients with RA who achieve remission are unclear. We compared the incidence of radiographic progression in patients with RA who did and did not experience flare after etanercept (ETN) reduction/withdrawal. Methods: Eligible adults with moderately active RA despite MTX received ETN 50 mg plus MTX weekly in a 36-week, open-label induction period; patients achieving sustained low disease activity by week 36 were randomized to ETN 50 mg plus MTX, ETN 25 mg plus MTX, or placebo plus MTX in a 52-week, double-blind maintenance period. In post hoc analyses, radiographic progression (Δ modified total Sharp score ⩾0.5 units/year) was compared in patients with and without flare [based on DAS28 relapse (main analysis), and clinical disease activity index and simplified disease activity index relapse (sensitivity analyses)]. Findings from patients receiving full- and reduced-dose combination therapy were pooled for comparison with those from patients receiving MTX only. Results: Significantly more patients receiving MTX monotherapy experienced flare, defined as DAS28 relapse (62% vs 21%; P < 0.0001) and radiographic progression (17% vs 9%; P < 0.001), than patients receiving full-/reduced-dose combination therapy in the double-blind period. Patients with flare defined as clinical disease activity index and simplified disease activity index relapse had higher rates of radiographic progression than those without flare in the full-/reduced-dose combination therapy group ( P < 0.01). Conclusion: Radiographic progression may be a consequence of flare after biologic DMARD dose reduction/withdrawal in patients with RA. If these approaches are taken, careful monitoring for signs/symptoms of relapse is needed. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00565409.